ANTIHYPERTENSION STUDY OF ANREDERA CORDIFOLIA (TEN). V. STEENIS EXTRACT AND ITS FRACTIONS IN RATS THROUGH DEXAMETHASONE INDUCTION AND NITRIC OXIDE RELEASE. - Garmana, Afrillia Nuryanti; Sukandar, Elin Yulinah; Fidrianny, Irda (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aims of this study were to prove the antihypertensive effect of Anredera cordifolia (Madeira vine) in dexamethasone-induced hypertensive rat and to determine the release of nitric oxide (NO). Methods: The rat's blood pressure was measured by CODAÂ® tail-cuff blood pressure system. A hypertensive rat model was developed on day 7 after administration of dexamethasone injection 0.5 mg/kg body weight (bw). NO levels were measured by spectrophotometry at a wavelength of 546 nm after reacting the serum sample with Griess reagent. Results: Ethanol extract of Madeira vine (EEMV), ethyl acetate fraction (EF), and water fraction (WF) could reduce systolic blood pressure at day 14 with a diastolic blood pressure (DBP) reduction of 26.8, 34.1, and 40.5 mmHg, respectively. DBP began to decrease from day 8 in the EEMV group with a DBP reduction of 24.1 mmHg. In the HF, EF, and WF groups, decreasing in DBP occurred on day 14 which were 22.0, 24.5, and 35.4 mmHg, respectively. NO level in rat serum was increased significantly at 90 min after administration of EEMV 100 mg/kg bw and WF 40.73 mg/kg bw. Increasing in NO levels due to EF with a dose of 1.66 mg/kg bw was not significantly different to control group. Conclusion: Ethanol extract of A. cordifolia had the antihypertensive effect in dexamethasone-induced hypertensive rats, so does its WF and EF. The mechanism of ethanol extract of Madeira vine leaves and its WF most likely due to vasodilation effect through NO-pathway, whereas EF could have other mechanism(s) of action. Â